Pain: from physiopathology to bio-psycho-social model - Francesco Amato (Pathos)
Pain management represents one of the most challenging aspects of medicine and a fundamental part of disease management. The sensation of pain is the result of a complex interaction between peripheral nerves and the central nervous system. However, pharmacological and non-pharmacological strategies are not always effective. Our observations suggest that emotions, nostalgia, cultural and ethnic differences, and relationships with others may serve as potential mechanisms of analgesia, influencing the efficacy of pharmacological treatment.